2007
DOI: 10.1159/000098080
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Renal Cancer with Tfe3 Gene Fusion in an Elderly Man

Abstract: Sporadic cases of a particular group of renal cancers associated with a translocation involving Xp11.2, known as the TFE3 transcription factor gene, have been reported in the last 20 years. The group was also classified in 2004 WHO kidney carcinoma classifications. A 79-year-old male patient was investigated at the outpatient department for gross intermittent hematuria. Sonography showed a spherical left kidney with increased total size, without evidence of the corticomedullary differentiation due to parenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…In addition to a recent group of renal tumors labeled renal carcinomas associated with Xp11.2 translocations/TFE3 gene fusions that has been included in the latest (2004) World Health Organization classification of renal tumors, the existence of another group of translocation associated renal neoplasms has become apparent [1][2][3]. This subset of renal tumors displays a balanced translocation t(6;11), first described in 1996 by Dijkhuizen at al [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a recent group of renal tumors labeled renal carcinomas associated with Xp11.2 translocations/TFE3 gene fusions that has been included in the latest (2004) World Health Organization classification of renal tumors, the existence of another group of translocation associated renal neoplasms has become apparent [1][2][3]. This subset of renal tumors displays a balanced translocation t(6;11), first described in 1996 by Dijkhuizen at al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Citations of articles used in the table: Argani et al 2007 Rais-Bahrami et al 2007 LaGrange et al 2007 Franzini et al 2007 Hora et al 2008 Camparo et al 2008 Hora et al 2009 Suarez-Vilela et al 2011, Koie et al 2009 Armah et al 2009 Kuroda et al 2010 Choueiri et al 2010 Ishihara et al 2011 Liu et al 2011 Nelius et al 2011 Numakura et al 2011, Kato et al 2011 Klatte et al 2012 Morii et al 2012 Rao et al 2012 Inamura et al 2012 Arnoux et al 2012 Komai et al 2009 Gaillot-Durand et al 2013.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, its incidence is very low in adults, and Komai et al [7] reported that Xp11 translocation RCC was found in only 7 of 443 adult RCC patients. Although Xp11.2 translocation RCC has a relatively good prognosis in pediatric cases, adult-onset Xp11.2 translocation RCC is reported to have a poor prognosis [2,7,8] . The reasons for this include the fact that most patients have an advanced clinical stage at diagnosis and also that there is a lack of effective systemic therapy.…”
Section: Xp112 Translocation Rcc Was Recognized In the 2004mentioning
confidence: 99%